Improving Speaking Skills Through Role Play Method Among Eighth Grade Students of SMP Insan Madani - Mariyanah, Siti (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study aims to examine the extent to which the role play method can enhance the speaking skills of eighth-grade students at SMP Insan Madani in English language learning. Speaking is one of the essential components of language proficiency and often poses a challenge for students, particularly in terms of fluency, pronunciation, and self-confidence. The role play method was chosen due to its ability to foster an engaging, active, and contextual learning environment. The research applied a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data collection techniques included observation, interviews, and pre- and post-tests of students' speaking abilities. The findings revealed significant improvements in students’ fluency, confidence in expressing opinions, and mastery of vocabulary and sentence structures. Consequently, the role play method has proven effective in enhancing speaking skills and is recommended as an alternative instructional strategy for English language teaching at the junior high school level.